Effects of a Balance Training Program Using a Foam Rubber Pad in Community-Based Older Adults. Issue 2 (April 2015) - Hirase, Tatsuya; Inokuchi, Shigeru; Matsusaka, Nobuou; Okita, Minoru
<x xml:space="preserve">Abstract</x> Background and Purpose: Exercise programs aimed at improving balance are effective in fall prevention for older adults. Guidelines indicate that unstable elements should be integrated in balance training with this population. Balance training on an unstable surface facilitates proprioception mediated by skin receptors in the soles of the feet and by mechanoreceptors in the joints and muscles. This randomized controlled trial examined whether balance training performed using a foam rubber pad was more beneficial than balance training performed on a stable flat surface in older adults. Methods: Older adults using Japanese community day centers once or twice per week were enrolled in this trial. In total, 93 participants were randomized to 1 of 3 groups: foam rubber exercise group (n = 32), stable surface exercise group (n = 31), and control group (n = 30). Participants in the foam rubber and stable surface exercise groups attended a 60-minute exercise class once a week for 4 months and followed a home-based exercise routine. Outcome measures were the following performance tests: the one-leg standing test (OLST), the chair standing test, the timed up-and-go test (TUGT), and the tandem-stance test (TST). These assessments were conducted before the intervention, and at 1, 2, 3, and 4 months after starting the intervention. Results: There were group × time interactions (P < 0.001) for all performance tests. The foam rubber exercise group showed significant improvements in the OLST, TST, and TUGT at 1 to 4 months compared with the control group (P < 0.02). The foam rubber exercise group also showed significant improvements in the OLST and TST at 2 and 3 months compared with the stable surface exercise group (P < 0.02). Within the foam rubber exercise group, the OLST, TUGT, and TST, at 1 to 4 months, were significantly improved compared with before the intervention (P < 0.01). Within the stable surface exercise group, the TUGT and TST, at 3 and 4 months, were significantly improved compared with before the intervention (P < 0.01). Conclusions: This study confirms that balance training in older adults performed using a foam rubber pad is effective for improving balance ability, and that this improvement occurs 2 months earlier compared with balance training performed on a stable surface. These findings suggest that balance training performed using a foam rubber pad is beneficial to clients and service providers because the programs improve physical functioning with a reduced number of exercise sessions.